Prandial States Modify the Reactivity of the Gustatory Cortex Using Gustatory Evoked Potentials in Humans - Jacquin-Piques, Agnès; Gaudillat, Stéphanie; Mouillot, Thomas; Gigot, Vincent; Meillon, Sophie; Leloup, Corinne; Penicaud, Luc; Brondel, Laurent (Frontiers in Neuroscience, 2016)
Previous functional Magnetic Resonance Imaging studies evaluated the role of satiety on cortical taste area activity and highlighted decreased activation in the orbito-frontal cortex when food was eaten until satiation. The modulation of orbito-frontal neurons (secondary taste area) by ad libitum food intake has been associated with the pleasantness of the food’s flavor. The insula and frontal operculum (primary taste area) are also involved in reward processing. The aim was to compare human gustatory evoked potentials (GEP) recorded in the primary and secondary gustatory cortices in a fasted state with those after food intake. Fifteen healthy volunteers were enrolled in this observational study. In each of two sessions, two GEP recordings were performed (at 11:00 am and 1:30 pm) in response to sucrose gustatory stimulation, and a sucrose-gustatory threshold was determined. During one session, a standard lunch was provided between the two GEP recordings. During the other session, subjects had nothing to eat. Hunger sensation, wanting, liking and the perception of the solution’s intensity were evaluated with visual analogue scales. GEP latencies measured in the Pz (p<0.001), Cz (p<0.01), Fz (p<0.001) recordings (primary taste area) were longer after lunch than in the pre-prandial condition. Fp1 and Fp2 latencies (secondary taste area) tended to be longer after lunch, but the difference was not significant. No difference was observed for the sucrose-gustatory threshold regardless of the session and time. Modifications in the primary taste area activity during the post-prandial period occurred regardless of the nature of the food eaten and could represent the activity of the frontal operculum and insula, which was recently shown to be modulated by gut signals (GLP-1, CCK, ghrelin, or insulin) through vagal afferent neurons or metabolic changes of the internal milieu after nutrient absorption. This trial was registered at clinicalstrials.gov as NCT02472444.